Seek and You Shall Find. A Neuropsychoanalytic Perspective on Seeking (Revista de Psicología, 2025)
This lecture is part of a webinar organized by the Turning Point Foundation for Health and Sustainability represented by its president, Dr. Andrea Rodriguez Quiroga, with the aim of promoting research-based clinical training. This webinar lasted two hours and consisted of a presentation of the theory in relation to SEEKING as an affect, its neuropsychoanalytic background and its clinical application. Finally, a clinical case was presented but is not reproduced in this paper for confidentiality reasons.
Keywords: neuropsychoanalysis; affect; seeking; homeostasis; mood disorders